PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POP-UP BOOK PADA PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR - Kristian Federik Dongoran; Siti Halidjah; Suparjan Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis development research was carried out to produce a product in the form of pop-upbook based learning media in class V theme 1 sub-theme 2 learning 2 learning materialthe human skeleton. The research method used is research and development (R&D)adaptation research and development by Borg and Gall. The sources of this research are,interview, expert validation, student feedback, and documentation during the use of pop-up book based learning media. The data collecting technique in this research anddevelopment are interview and questionnaires. The results of research and developmentshow that the process of developing pop-up book based learning media has gone through7 research steps, Research and information collecting, Planing, Develop primary from ofproduct, Preliminary field testing produk, Main product revision, Main field testing,Operational product revision. The feasibility level of pop-up book based learning media is“Very Good” seen from the aspect of design with average value 3,79 and seen form theaspect of content with average value 4,00 as well as product trial result “Very Good” withaverage value 3,58.Keywords: Lerning Media, Pop-Up Book, Thematic learning